Glasgow Coma Scale: Tinjauan terhadap Kegunaan, Keterbatasan, dan Perkembangannya - Aquila Graham; Setiorini, Anggi; Septiani, Linda; Perdani, Roro Rukmi Windi (CV. Jasa Sukses Abadi, 2025)
The Glasgow Coma Scale (GCS) is a widely used neurological assessment tool for evaluating the level of consciousness in patients with brain injury. Introduced in 1974 by Teasdale and Jennett, it has become a standard in emergency departments, intensive care units, and neurosurgical wards worldwide. The GCS assesses patient responses in three domains: eye opening, verbal response, and motor response, with scores ranging from 3 (deep coma) to 15 (fully conscious). The GCS score is used to classify the severity of Traumatic Brain Injury (TBI) and predict clinical outcomes. However, several studies have highlighted limitations of the GCS, particularly in predicting patient outcomes and its application in specific populations. This article provides a critical review of the GCS, including its utility, limitations, and ongoing modifications and developments.